2001
DOI: 10.1046/j.1365-2109.2001.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid and reproduction in fish: endocrine regulation and gamete quality

Abstract: High ascorbic acid concentrations have been associated with gonad and brain tissues in teleost fishes. Although a direct dietary effect on gamete quality has been given some attention recently, the mechanism of action of ascorbate along the cascade of reproductive events in the hypothalamus, pituitary and gonads has not been defined. Data relating to gamete production and quality, as well as a possible protective role for ascorbate against cumulative genetic defects during gametogenesis and congenital malforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 100 publications
(153 reference statements)
2
32
0
2
Order By: Relevance
“…High ascorbic acid concentrations have been associated with gonad tissues in teleost fishes (44,45). Since ascorbic acid together with R-tocopherol is considered to be critical for the normal development of fish embryos (45)sas data obtained from cultured fish studies revealed (34, 45)ssuch a distribution is not surprising.…”
Section: Resultsmentioning
confidence: 88%
“…High ascorbic acid concentrations have been associated with gonad tissues in teleost fishes (44,45). Since ascorbic acid together with R-tocopherol is considered to be critical for the normal development of fish embryos (45)sas data obtained from cultured fish studies revealed (34, 45)ssuch a distribution is not surprising.…”
Section: Resultsmentioning
confidence: 88%
“…It has already been demonstrated that nutrition (composition of diet) can affect the male reproductive performance in fish (see review by Izquierdo et al 2001). Dabrowski and Ciereszko (2001) and Lee and Dabrowski (2004) showed that vitamins E and C have an important protective role for the sperm cells during spermatogenesis (an antioxidant function) and improve sperm quality, resulting in higher fertilization and hatching rates, and these effects are influenced by season. It was also shown that the spermatozoa contain a high level of polyunsaturated fatty acids (PUFAs), which is evident in the phospholipids (Labbe et al 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Improvement of broodstock nutrition and feeding greatly enhances the quality of both sperm and eggs (Dabrowski and Ciereszko 2001;Izquierdo et al 2001). Moreover, most studies of fish farms have focused on the management of female broodfish, while the effects of nutrition on male spawning performance remain poorly understood (Alavi et al 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, 357 mg/kg ascorbic acid is required to obtain a 90% level of saturation and led to highest fecundity and embryo survival for rainbow trout (Oncorhynchus mykiss) [12]. The antioxidant effect of ascorbic acid seems to be critical for the genes integrity of fish gametes and decrease sperms DNA Fragmentation., meanwhile insufficient ascorbic acid lead to damage during mitotic division of germ cell [9,22]. Ascorbic acid is a leading nutrient in different tissue of reproductive system where interaction between catecholamine and steroid hormones that involved in gonad growth, acts as a regulatory mechanism of ascorbate absorption and metabolism in reproductive system [9].…”
Section: Resultsmentioning
confidence: 99%
“…A dietary supplement of ascorbic acid has positive effects on reproductive performance in various fish species as it is involved in reproductive functions of fish tissues [9]. Vitamin C affects hormone synthesis, vitellogenesis, and results in variable oocyte AA retention and gamete quality [10].…”
Section: Introductionmentioning
confidence: 99%